Increasing English Reading Comprehension Through Literary Text Extensive Reading Program - Euis Meinawati; Sufi Alawiyah; Herlin Widasiwi Setianingrum; Prapti Wigati Purwaningrum; Chodidjah Chodidjah (VELES Voices of English Language Education Society, 2022)
The research objective is to improve reading comprehension skills through an extensive program of reading literary texts. It used a mixed method. Research participants are 5th-semester students who receive extensive reading (2) courses in the 2020-2021 academic year at Universitas Bina Sarana Informatika Jakarta as many as 70 students. There are two data used in this study, namely 1) qualitative data taken using a questionnaire. Qualitative data were analyzed using transcribed and encoded, organized, categorized, and taking concluding. 2) Quantitative data were taken from the pre-test and post-test. The test data were analyzed using a t-test. The results of the study show that overall an extensive reading program with literary texts has an impact on improving English reading comprehension. Students also have a positive perception of the extensive reading program because they can build interest in reading and reading habits